Design and implementation of a novel spherical robot with rolling and leaping capability. (May 2022) - Chang, Wei-Jer; Chang, Chih-Ling; Ho, Jen-Hung; Lin, Pei-Chun
Highlights: Development of a spherical robot that can leap while rolls. Using a five-bar linkage mechanism and a release/retract mechanism for leaping. Using a differential drive to actuate two semi spheres for rolling and turning. Dynamics of rolling and leaping are analyzed. The robot can leap up to 1.14-times of radius to overcome a barrier while rolls. Abstract: To improve robots' mobility on flat ground and rough terrain, we designed and implemented a novel spherical robot with a combined rolling and leaping capability. The robot has two individually driven semi-spheres, which generate rolling and turning motions. The robot also has a five-bar linkage with a release/retract mechanism for leaping. The release/retract mechanism only uses one DOF to control and switch the mechanism in three different stages: retracting, maintaining, and releasing. In this paper, the dynamics of the robot in rolling and leaping are analyzed. The robot was empirically built, and its performance was experimentally evaluated. The results confirm that the robot can leap close to 25.4 cm diameter of the sphere, which, to the best of our knowledge, is the best among reported spherical robots. The robot can also leap while rolling over a 14 cm barrier, which is equal to 1.14 times the sphere's radius. Graphical abstract: Image, graphical abstract